COMBINATION OF BROWNING INHIBITOR SUBSTANCE AND SUCROSE ON THE GROWTH OF MAS KIRANA BANANA PLANLET(Musa acuminata C.) IN VITRO - Dofan Rizki Baskara; Ari Wijayani; Rina Srilestari (Jurnal Agrivet, 2018)
Mas Kirana Banana (Musa acuminata C.) is one of the most popular tropical fruit plants in the community. The problem of banana tissue culture is browning on the media against phenolic substances that need to be done before the browning inhibitor. This study was conducted to determine the effect of browning inhibitor substance and sucrose on the growth of plantlet banana mas kirana. Research method with RAL (Completely Random Design) two factors + 1 control. The first ingredient consisted of 3 levels, namely polyvinylpyrrolidone 75 g / L, Vitamin C 0,50 ppm, Active Charcoal 1 g / L, while the second factor consisted of 3 levels, sucrose 15 g / L, 20 g / L and 25 g / L Each treatment was repeated 3 times. Data with anova and test with DMRT at 5% level. Browning inhibitors Vitamin C results in the number of shoots, wet weight,  dry weight  and  browning level compared with polyvinylpyrrolidone and activated charcoal. The addition of sucrose concentrations of 20 g / L canincrease length of rootKeywords: Banana, tissue culture, browning inhibitor substance, sucrose